Calculation of Limestone Reserves in the East Biluhu Region, Gorontalo district, Gorontalo Province - Widya Annisa; Muhammad Kasim; Intan Noviantari Manyoe (Penerbitan Universitas Trisakti, 2021)
Indonesia is a country that has a lot of natural resources. Natural resources are widely used in various areas of human life. One of the resources that is often used is limestone. Limestone is a non-metallic mining material that has considerable potential and reserves and spreads across almost all parts of Indonesia, but the exact amount of reserves is not yet known. The research aims to predict the amount of packstone-type limestone reserves using geophysical methods. This research was conducted using the geoelectric method with the Schlumberger configuration, where the resistivity geoelectric data obtained variations in resistivity and layer thickness. From this data, it is then interpreted to determine the type of rock in the surface area, and making a 3D model to determine the distribution of limestone in the study area and to calculate the amount of limestone reserves in the study area. Based on the research results, it is known that the research area is dominated by packstone with a resistivity value of 16.6 Ωm - 1.3x105 Ωm. The calculation result of packstone reserves in the study area is 73,629,403tons.